Altman Z-Score Analysis in Predicting Financial Distress and Its Impact on Firm Value: Evidence from Property Sector Companies Listed on the Indonesia Stock Exchange (2022–2024) - Muhammad Figo Yosawiyata; P. Pujiono (Manunggal Halim Jaya, 2027)
This study examines the effect of financial distress, measured by the Altman Z-Score, on firm value among property sector companies listed on the Indonesia Stock Exchange during 2022–2024. Liquidity, operating cash flow, and leverage are included as control variables to provide a more comprehensive understanding of the determinants of firm value. Using a quantitative approach, this study employs secondary data obtained from annual financial statements. The sample was selected through purposive sampling, resulting in 132 firm-year observations. Data were analyzed using multiple linear regression with IBM SPSS Statistics 27. The results indicate that the Altman Z-Score, liquidity, operating cash flow, and leverage have positive and significant effects on firm value proxied by Tobin’s Q. These findings suggest that firms with stronger financial health, better short-term solvency, stable operating cash flows, and effective debt management tend to achieve higher market valuations. The study supports signaling theory and agency theory, highlighting the importance of financial information in investors’ assessments of corporate prospects. Practically, the findings imply that managers should maintain financial health, improve operating cash flow quality, and optimize leverage management to enhance firm value and strengthen investor confidence.